Efecto de la división del trabajo doméstico no remunerado (TDNR), del trabajo de cuidado no remunerado (TCNR) y de las actitudes de género sobre las preferencias de fecundidad de las mujeres en Colombia - Marcela Eugenia Alvear Portaccio (2019)
The effect of gender relations -measured through the distribution of Unpaid Domestic Work (UDW) and Unpaid Care Work (UCW)-, as well as attitudes about women's fertility preferences is a relatively recent line of study within the fertility literature. Most of the evidence comes mainly from Europe and the United States, while in Latin American countries this association has not been examined. In this sense, the objective of this study is to examine how gender inequality within the couple (distribution of UDW and UCW) and gender attitudes about women's reproductive-productive roles affect their preferences for having a second birth in Colombia. The information comes from Colombia's 2015 Demographic and Health Survey (DHS). The sample under study is composed of married and/or cohabiting women with a child under 5 years of age, who were classified as traditional, egalitarian and traditional-traditional according to the division of UDW and UCW, and as progressive and conservative according to their gender attitudes. The main results are: 1) the division of UDW does not play any role in the fertility preferences of married and/or cohabiting women. In other words, regardless of unequal or egalitarian distribution, the UDW does not enter the matrix of variables at the time of wanting to have a second birth. 2) On the other hand, women with equal arrangements with their partners in the UCW are more likely to want a second birth than women with traditional arrangements. 3) Women with progressive attitudes are less likely to want a second birth than those with conservative attitudes. 4) Women who are more inconsistent in their attitudes-behaviors - progressive women in their imaginary versus their reproductive role, but with asymmetric arrangements in the UCW - are less likely to want to have a second birth compared to conservative-recharged ones.